An exploratory study on "hanging out" among selected male and female freshmen in the College of Home Economics, University of the Philippines Diliman - Manlapig, Ana Patricia M. (College of Home Economics, University of the Philippines Diliman, 2013)
This study determined the definition of the term "hanging out" by male and female freshmen and identified the types of activities it involves. Moreover, it sought to determine the frequency in a week freshmen spend "hanging out", the people who they are with when "hanging out", and the places where they "hang out". By referral, thirty-six (36) freshmen (16 males, 20 females), age 16 to 19 years agreed to participate in the study through interviews. Using frequency distribution tables and percentage values, data gathered were analyzed and categorized into themes. Results showed that male and female freshmen give similar but loose definitions to "hanging out". However, male freshmen regard "hanging out" as more of a way to have fun and relaxation while female freshmen pertain to it as an opportunity to relate and socialize with other people. Results also showed that male and and female freshmen engage in different types of "hanging out" activities such as leisure, verbal communication, physical and academic related. In general, freshmen engage in leisure type of "hanging out" activities such as going to malls, eating out, watching movies, and playing video games. Freshmen also reported that "hanging out" can be done not only with peers but with members of their families as well. On the other hand, the frequency of "hanging out" among freshmen varies depending on their class schedule, school workload, and people they are with. Lastly, results identified that "hanging out" could be done in leisure spaces, living spaces, and university grounds. This study recommends the sue of a wider research site and sample, different data gathering methods and theoretical frameworks to acquire further knowledge on the definition of "hanging out" and the activities it involves.